PROBLEMS IN RUNNING A TUBERCULOSIS DISPENSARY IN A DEVELOPING-COUNTRY - TURKEY - GOKCE, C; GOKCE, O; ERDOGMUS, Z; ARISOY, E; ARISOY, S; KOLDAS, O; ORUC, A (Churchill Livingstone, 1991)
Declining use of the services of local dispensaries has often been suggested as a significant factor in the rising trend of tuberculosis in Turkey after 1970. Data confirming this view were insufficient until this study, which consists of an evaluation of the records of 51 086 subjects seen by the tuberculosis dispensary in Elazig between 1985-1989. We found that, despite an expected yearly population increase, there were no significant differences in the numbers of diagnostic and follow-up procedures as well as preventive and therapeutic interventions recorded in different years, and that cases of active tuberculosis lost to follow-up had gradually increased. The least effective method of case-finding, mass screening, had been employed most frequently. These results revealed a less than optimum use of the services of the tuberculosis dispensary and prompted us to suggest the following changes: (1) diversion of economic resources currently used for mass screening in order to use them for better purposes; (2) functional integration of tuberculosis dispensaries with local, general or university hospitals, since a separate system for tuberculosis care is accompanied by a segregating and stigmatising effect for all concerned; (3) entering all patients and contacts into a computerised database to alleviate the problems associated with inadequate follow-up. We conclude that existing control programmes should be reviewed and improved to prevent an increase of tuberculosis, particularly in developing countries like Turkey.
Keywords: Infection